Dual quantum confinement and anisotropic spin splitting in the multivalley semimetal PtSe2 - Clark, O. J.; Mazzola, F.; Feng, J.; Sunko, Veronika; Marković, I.; Bawden, L.; Kim, T. K.; King, P. D. C.; Bahramy, M. S. (Physical Review B)
We investigate the electronic structure of a two-dimensional electron gas created at the surface of the multivalley semimetal 1⁢T −PtSe2. Using angle-resolved photoemission and first-principles-based surface space-charge calculations, we show how the induced quantum well sub-band states form multiple Fermi surfaces, which exhibit highly anisotropic Rashba-like spin splittings. We further show how the presence of both electronlike and holelike bulk carriers causes the near-surface band bending potential to develop an unusual nonmonotonic form, with spatially segregated electron accumulation and hole accumulation regions, which in turn amplifies the induced spin splitting. Our results thus demonstrate the novel environment that semimetals provide for tailoring electrostatically induced potential profiles and their corresponding quantum sub-band states.

How to Sheafify an Elliptic Quantum Group - Yang, Yaping; Zhao, Gufang (2017 MATRIX Annals)
These lecture notes are based on Yang’s talk at the MATRIX program Geometric R-Matrices: from Geometry to Probability, at the University of Melbourne, Dec. 18–22, 2017, and Zhao’s talk at Perimeter Institute for Theoretical Physics in January 2018. We give an introductory survey of the results in Yang and Zhao (Quiver varieties and elliptic quantum groups, 2017. arxiv1708.01418). We discuss a sheafified elliptic quantum group associated to any symmetric Kac-Moody Lie algebra. The sheafification is obtained by applying the equivariant elliptic cohomological theory to the moduli space of representations of a preprojective algebra. By construction, the elliptic quantum group naturally acts on the equivariant elliptic cohomology of Nakajima quiver varieties. As an application, we obtain a relation between the sheafified elliptic quantum group and the global affine Grassmannian over an elliptic curve.

The Essential Role of Thermodynamics in Metabolic Network Modeling: Physical Insights and Computational Challenges - De Martino, A; De Martino, Daniele; Marinari, E (Chemical Kinetics)
Quantitative studies of cell metabolism are often based on large chemical reaction network models. A steady-state approach is suited to analyze phenomena on the timescale of cell growth and circumvents the problem of incomplete experimental knowledge on kinetic laws and parameters, but it should be supported by a correct implementation of thermodynamic constraints. In this chapter, we review the latter aspect, highlighting its computational challenges and physical insights. The simple introduction of Gibbs inequalities avoids the presence of unfeasible loops allowing for correct timescale analysis, but leads to possibly non-convex feasible flux spaces whose exploration needs efficient algorithms. We briefly review the implementation of thermodynamics through variational principles in constraint-based models of metabolic networks.

Aktionspotenzial: Fortleitung im Axon - Jonas, Peter M (Physiologie des Menschen)
Neurone empfangen Eingangssignale, konvertieren diese in Aktionspotenziale und generieren schließlich Ausgangssignale auf ihren Zielzellen. Dabei sind die zu überwindenden räumlichen Distanzen oft groß. Daher ist entscheidend, dass elektrische Signale in Nervenzellen schnell von einem zum anderen Ort geleitet werden können. Diese wichtige Aufgabe erfüllt das Axon, der „Ausgangsfortsatz“ der Nervenzelle. Für die schnelle Leitung des Aktionspotenzials sind sowohl die passiven Eigenschaften des axonalen Kabels als auch die aktiven Eigenschaften der Zellmembran von entscheidender Bedeutung. Die Evolution bedient sich zweier Tricks, um die Leitungsgeschwindigkeit des Aktionspotenzials zu maximieren. Der eine Trick ist die Zunahme des Axondurchmessers. Der andere Trick ist die Ausbildung von Markscheiden. Dies führt bei nahezu gleichem Platzbedarf zu einer Zunahme der Leistungsgeschwindigkeit um fast zwei Größenordnungen. Die Aktionspotenzialleitung an myelinisierten Axonen erfolgt „saltatorisch“.

Leptin’s hunger-suppressing effects are mediated by the hypothalamic–pituitary–adrenocortical axis in rodents - Perry, Rachel J.; Resch, Jon M.; Douglass, Amelia May Barnett; Madara, Joseph C.; Rabin-Court, Aviva; Kucukdereli, Hakan; Wu, Chen; Song, Joongyu D.; Lowell, Bradford B.; Shulman, Gerald I. (Proceedings of the National Academy of Sciences)
Leptin informs the brain about sufficiency of fuel stores. When insufficient, leptin levels fall, triggering compensatory increases in appetite. Falling leptin is first sensed by hypothalamic neurons, which then initiate adaptive responses. With regard to hunger, it is thought that leptin-sensing neurons work entirely via circuits within the central nervous system (CNS). Very unexpectedly, however, we now show this is not the case. Instead, stimulation of hunger requires an intervening endocrine step, namely activation of the hypothalamic–pituitary–adrenocortical (HPA) axis. Increased corticosterone then activates AgRP neurons to fully increase hunger. Importantly, this is true for 2 forms of low leptin-induced hunger, fasting and poorly controlled type 1 diabetes. Hypoglycemia, which also stimulates hunger by activating CNS neurons, albeit independently of leptin, similarly recruits and requires this pathway by which HPA axis activity stimulates AgRP neurons. Thus, HPA axis regulation of AgRP neurons is a previously underappreciated step in homeostatic regulation of hunger.

Ranks, 2-Selmer groups, and Tamagawa numbers of elliptic curves with ℤ∕2ℤ × ℤ∕8ℤ-torsion - Chan, Yik Tung; Hanselman, Jeroen; Li, Wanlin (The Open Book Series)
In 2016, Balakrishnan, Ho, Kaplan, Spicer, Stein and Weigandt produced a database of elliptic curves over Q ordered by height in which they computed the rank, the size of the 2-Selmer group, and other arithmetic invariants. They observed that after a certain point, the average rank seemed to decrease as the height increased. Here we consider the family of elliptic curves over Q whose rational torsion subgroup is isomorphic to Z∕2Z×Z∕8Z. Conditional on GRH and BSD, we compute the rank of 92% of the 202,461 curves with parameter height less than 103. We also compute the size of the 2-Selmer group and the Tamagawa product, and prove that their averages tend to infinity for this family.

Harmonic dynamics of the Abelian sandpile - Lang, Moritz; Shkolnikov, Mikhail (Proceedings of the National Academy of Sciences of the United States of America)
The abelian sandpile serves as a model to study self-organized criticality, a phenomenon occurring in biological, physical and social processes. The identity of the abelian group is a fractal composed of self-similar patches, and its limit is subject of extensive collaborative research. Here, we analyze the evolution of the sandpile identity under harmonic fields of different orders. We show that this evolution corresponds to periodic cycles through the abelian group characterized by the smooth transformation and apparent conservation of the patches constituting the identity. The dynamics induced by second and third order harmonics resemble smooth stretchings, respectively translations, of the identity, while the ones induced by fourth order harmonics resemble magnifications and rotations. Starting with order three, the dynamics pass through extended regions of seemingly random configurations which spontaneously reassemble into accentuated patterns. We show that the space of harmonic functions projects to the extended analogue of the sandpile group, thus providing a set of universal coordinates identifying configurations between different domains. Since the original sandpile group is a subgroup of the extended one, this directly implies that it admits a natural renormalization. Furthermore, we show that the harmonic fields can be induced by simple Markov processes, and that the corresponding stochastic dynamics show remarkable robustness over hundreds of periods. Finally, we encode information into seemingly random configurations, and decode this information with an algorithm requiring minimal prior knowledge. Our results suggest that harmonic fields might split the sandpile group into sub-sets showing different critical coefficients, and that it might be possible to extend the fractal structure of the identity beyond the boundaries of its domain.

Bi-Sobolev solutions to the prescribed Jacobian inequality in the plane with L p data and applications to nonlinear elasticity - Fischer, Julian L; Kneuss, Olivier (Journal of Differential Equations)
We construct planar bi-Sobolev mappings whose local volume distortion is bounded from below by a given function f∈Lp with p>1. More precisely, for any 1<q<(p+1)/2 we construct W1,q-bi-Sobolev maps with identity boundary conditions; for f∈L∞, we provide bi-Lipschitz maps. The basic building block of our construction are bi-Lipschitz maps which stretch a given compact subset of the unit square by a given factor while preserving the boundary. The construction of these stretching maps relies on a slight strengthening of the celebrated covering result of Alberti, Csörnyei, and Preiss for measurable planar sets in the case of compact sets. We apply our result to a model functional in nonlinear elasticity, the integrand of which features fast blowup as the Jacobian determinant of the deformation becomes small. For such functionals, the derivation of the equilibrium equations for minimizers requires an additional regularization of test functions, which our maps provide.

Protein dynamics regulate distinct biochemical properties of cryptochromes in mammalian circadian rhythms - Fribourgh, Jennifer L.; Srivastava, Ashutosh; Sandate, Colby R.; Michael, Alicia; Hsu, Peter L.; Rakers, Christin; Nguyen, Leslee T.; Torgrimson, Megan R.; Parico, Gian Carlo G.; Tripathi, Sarvind; Zheng, Ning; Lander, Gabriel C.; et al. (bioRxiv)
Circadian rhythms are generated by a transcription-based feedback loop where CLOCK:BMAL1 drive transcription of their repressors (PER1/2, CRY1/2), which bind to CLOCK:BMAL1 to close the feedback loop with ~24-hour periodicity. Here we identify a key biochemical and structural difference between CRY1 and CRY2 that underlies their differential strengths as transcriptional repressors. While both cryptochromes bind the BMAL1 transactivation domain with similar affinity to sequester it from coactivators, CRY1 is recruited with much higher affinity to the PAS domain core of CLOCK:BMAL1, allowing it to serve as a stronger repressor that lengthens circadian period. We identify a dynamic loop in the secondary pocket that regulates differential binding of cryptochromes to the PAS domain core. Notably, PER2 binding remodels this loop in CRY2 to enhance its affinity for CLOCK:BMAL1, explaining why CRY2 forms an obligate heterodimer with PER2, while CRY1 is capable of repressing CLOCK:BMAL1 both with and without PER2.

A massive magnetic helium atmosphere white dwarf binary in a young star cluster - Richer, Harvey B.; Kerr, Ronan; Heyl, Jeremy; Caiazzo, Ilaria; Cummings, Jeffrey; Bergeron, Pierre; Dufour, Patrick (The Astrophysical Journal)
We have searched the Gaia DR2 catalog for previously unknown hot white dwarfs in the direction of young open star clusters. The aim of this experiment was to try and extend the initial–final mass relation (IFMR) to somewhat higher masses, potentially challenging the Chandrasekhar limit currently thought to be around 1.38 M⊙. We discovered a particularly interesting white dwarf in the direction of the young ∼150 Myr old cluster Messier 47 (NGC 2422). All Gaia indicators (proper motion, parallax, location in the Gaia color–magnitude diagram) suggest that it is a cluster member. Its spectrum, obtained from Gemini-South, yields a number of anomalies: it is a DB (helium-rich atmosphere) white dwarf, it has a large magnetic field (2.5 MG), is of high mass (∼1.06 M⊙), and its colors are very peculiar—particularly the redder ones (r, i, z and y), which suggests that it may have a late-type companion. This may be the only magnetized, detached binary white dwarf with a non-degenerate companion of any spectral type known in or out of a star cluster. If the white dwarf is a cluster member, as all indicators suggest, its progenitor had a mass just over 6 M⊙. It may, however, be telling an even more interesting story than the one related to the IFMR, one about the origin of stellar magnetic fields, SNe I, and gravitational waves from low-mass stellar systems.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

A multimass velocity dispersion model of 47 Tucanae indicates no evidence for an intermediate-mass black hole - Mann, Christopher R.; Richer, Harvey; Heyl, Jeremy; Anderson, Jay; Kalirai, Jason; Caiazzo, Ilaria; Möhle, Swantje D.; Knee, Alan; Baumgardt, Holger (The Astrophysical Journal)
In this paper, we analyze stellar proper motions in the core of the globular cluster 47 Tucanae to explore the possibility of an intermediate-mass black hole (IMBH) influence on the stellar dynamics. Our use of short-wavelength photometry affords us an exceedingly clear view of stellar motions into the very center of the crowded core, yielding proper motions for >50,000 stars in the central 2′. We model the velocity dispersion profile of the cluster using an isotropic Jeans model. The density distribution is taken as a central IMBH point mass added to a combination of King templates. We individually model the general low-mass cluster objects (main sequence/giant stars), as well as the concentrated populations of heavy binary systems and dark stellar remnants. Using unbinned likelihood model fitting, we find that the inclusion of the concentrated populations in our model plays a crucial role in fitting for an IMBH mass. The concentrated binaries and stellar-mass black holes (BHs) produce a sufficient velocity dispersion signal in the core so as to make an IMBH unnecessary to fit the observations. We additionally determine that a stellar-mass BH retention fraction of 8.5% becomes incompatible with our observed velocities in the core.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Intrinsic quantized anomalous Hall effect in a moiré heterostructure - Serlin, M.; Tschirhart, C. L.; Polshyn, Hryhoriy; Zhang, Y.; Zhu, J.; Watanabe, K.; Taniguchi, T.; Balents, L.; Young, A. F. (Science)
The quantum anomalous Hall (QAH) effect combines topology and magnetism to produce precisely quantized Hall resistance at zero magnetic field. We report the observation of a QAH effect in twisted bilayer graphene aligned to hexagonal boron nitride. The effect is driven by intrinsic strong interactions, which polarize the electrons into a single spin- and valley-resolved moiré miniband with Chern number C = 1. In contrast to magnetically doped systems, the measured transport energy gap is larger than the Curie temperature for magnetic ordering, and quantization to within 0.1% of the von Klitzing constant persists to temperatures of several kelvin at zero magnetic field. Electrical currents as small as 1 nanoampere controllably switch the magnetic order between states of opposite polarization, forming an electrically rewritable magnetic memory.
Keywords: multidisciplinary

Solids of quantum Hall skyrmions in graphene - Zhou, H.; Polshyn, Hryhoriy; Taniguchi, T.; Watanabe, K.; Young, A. F. (Nature Physics)
Partially filled Landau levels host competing electronic orders. For example, electron solids may prevail close to integer filling of the Landau levels before giving way to fractional quantum Hall liquids at higher carrier density1,2. Here, we report the observation of an electron solid with non-collinear spin texture in monolayer graphene, consistent with solidification of skyrmions3—topological spin textures characterized by quantized electrical charge4,5. We probe the spin texture of the solids using a modified Corbino geometry that allows ferromagnetic magnons to be launched and detected6,7. We find that magnon transport is highly efficient when one Landau level is filled (ν=1), consistent with quantum Hall ferromagnetic spin polarization. However, even minimal doping immediately quenches the magnon signal while leaving the vanishing low-temperature charge conductivity unchanged. Our results can be understood by the formation of a solid of charged skyrmions near ν=1, whose non-collinear spin texture leads to rapid magnon decay. Data near fractional fillings show evidence of several fractional skyrmion solids, suggesting that graphene hosts a highly tunable landscape of coupled spin and charge orders.
Keywords: General Physics and Astronomy

Large linear-in-temperature resistivity in twisted bilayer graphene - Polshyn, Hryhoriy; Yankowitz, Matthew; Chen, Shaowen; Zhang, Yuxuan; Watanabe, K.; Taniguchi, T.; Dean, Cory R.; Young, Andrea F. (Nature Physics)
Twisted bilayer graphene has recently emerged as a platform for hosting correlated phenomena. For twist angles near θ ≈ 1.1°, the low-energy electronic structure of twisted bilayer graphene features isolated bands with a flat dispersion1,2. Recent experiments have observed a variety of low-temperature phases that appear to be driven by electron interactions, including insulating states, superconductivity and magnetism3,4,5,6. Here we report electrical transport measurements up to room temperature for twist angles varying between 0.75° and 2°. We find that the resistivity, ρ, scales linearly with temperature, T, over a wide range of T before falling again owing to interband activation. The T-linear response is much larger than observed in monolayer graphene for all measured devices, and in particular increases by more than three orders of magnitude in the range where the flat band exists. Our results point to the dominant role of electron–phonon scattering in twisted bilayer graphene, with possible implications for the origin of the observed superconductivity.
Keywords: general physics and astronomy

Manipulating multivortex states in superconducting structures - Polshyn, Hryhoriy; Naibert, Tyler; Budakian, Raffi (Nano Letters)
We demonstrate a method for manipulating small ensembles of vortices in multiply connected superconducting structures. A micron-size magnetic particle attached to the tip of a silicon cantilever is used to locally apply magnetic flux through the superconducting structure. By scanning the tip over the surface of the device and by utilizing the dynamical coupling between the vortices and the cantilever, a high-resolution spatial map of the different vortex configurations is obtained. Moving the tip to a particular location in the map stabilizes a distinct multivortex configuration. Thus, the scanning of the tip over a particular trajectory in space permits nontrivial operations to be performed, such as braiding of individual vortices within a larger vortex ensemble—a key capability required by many proposals for topological quantum computing.
Keywords: mechanical engineering; condensed matter physics; general materials science; general chemistry; bioengineering

Tuning superconductivity in twisted bilayer graphene - Yankowitz, Matthew; Chen, Shaowen; Polshyn, Hryhoriy; Zhang, Yuxuan; Watanabe, K.; Taniguchi, T.; Graf, David; Young, Andrea F.; Dean, Cory R. (Science)
The discovery of superconductivity and exotic insulating phases in twisted bilayer graphene has established this material as a model system of strongly correlated electrons. To achieve superconductivity, the two layers of graphene need to be at a very precise angle with respect to each other. Yankowitz et al. now show that another experimental knob, hydrostatic pressure, can be used to tune the phase diagram of twisted bilayer graphene (see the Perspective by Feldman). Applying pressure increased the coupling between the layers, which shifted the superconducting transition to higher angles and somewhat higher temperatures.
Keywords: multidisciplinary

New correlated phenomena in magic-angle twisted bilayer graphene/s - Yankowitz, Mathew; Chen, Shaowen; Polshyn, Hryhoriy; Watanabe, K.; Taniguchi, T.; Graf, David; Young, Andrea F.; Dean, Cory R.; Sharpe, Aaron L.; Fox, E.J.; Barnard, A.W.; Finney, Joe (Journal Club for Condensed Matter Physics)
Since the discovery of correlated insulators and superconductivity in magic-angle twisted bilayer graphene (tBLG) ([1, 2], JCCM April 2018), theorists have been excitedly pursuing the alluring mix of band topology, symmetry breaking, Mott insulators and superconductivity at play, as well as the potential relation (if any) to high-Tc physics. Now a new stream of experimental work is arriving which further enriches the story. To briefly recap Episodes 1 and 2 (JCCM April and November 2018), when two graphene layers are stacked with a small rotational mismatch θ, the resulting long-wavelength moire pattern leads to a superlattice potential which reconstructs the low energy band structure. When θ approaches the “magic-angle” θM ∼ 1 ◦, the band structure features eight nearly-flat bands which fill when the electron number per moire unit cell, n/n0, lies between −4 < n/n0 < 4. The bands can be counted as 8 = 2 × 2 × 2: for each spin (2×) and valley (2×) characteristic of monolayergraphene, tBLG has has 2× flat bands which cross at mini-Dirac points.

Direct Imaging of magnetic structure in twisted bilayer graphene with scanning nanoSQUID-On-Tip microscopy - Serlin, Marec; Tschirhart, Charles; Polshyn, Hryhoriy; Zhu, Jiacheng; Huber, Martin E.; Young, Andrea (APS March Meeting 2019)
Bilayer graphene, rotationally faulted to ~1.1 degree misalignment, has recently been shown to host superconducting and resistive states associated with the formation of a flat electronic band. While numerous theories exist for the origins of both states, direct validation of these theories remains an outstanding experimental problem. Here, we focus on the resistive states occurring at commensurate filling (1/2, 1/4, and 3/4) of the two lowest superlattice bands. We test theoretical proposals that these states arise due to broken spin—and/or valley—symmetry by performing direct magnetic imaging with nanoscale SQUID-on-tip microscopy. This technique provides single-spin resolved magnetometry on sub-100nm length scales. I will present imaging data from our 4.2K nSOT microscope on graphite-gated twisted bilayers near the flat band condition and discuss the implications for the physics of the commensurate resistive states.

Spin wave transport through electron solids and fractional quantum Hall liquids in graphene - Zhou, Haoxin; Polshyn, Hryhoriy; Tanaguchi, Takashi; Watanabe, Kenji; Young, Andrea (APS March Meeting 2019)
In monolayer graphene, the interplay of electronic correlations with the internal spin- and valley- degrees of freedom leads to a complex phase diagram of isospin symmetry breaking at high magnetic fields. Recently, Wei et al. (Science (2018)) demonstrated that spin waves can be electrically generated and detected in graphene heterojunctions, allowing direct experiment access to the spin degree of freedom. Here, we apply this technique to high quality graphite-gated graphene devices showing robust fractional quantum Hall phases and isospin phase transitions. We use an edgeless Corbino geometry to eliminate the contributions of edge states to the spin-wave mediated nonlocal voltage, allowing unambiguous identification of spin wave transport signatures. Our data reveal two phases within the ν = 1 plateau. For exactly ν=1, charge is localized but spin waves propagate freely while small carrier doping completely quenches the low-energy spin-wave transport, even as those charges remain localized. We identify this new phase as a spin textured electron solid. We also find that spin-wave transport is modulated by phase transitions in the valley order that preserve spin polarization, suggesting that this technique is sensitive to both spin and valley order.

Normal state transport in superconducting twisted bilayer graphene - Polshyn, Hryhoriy; Zhang, Yuxuan; Yankowitz, Matthew; Chen, Shaowen; Taniguchi, Takashi; Watanabe, Kenji; Graf, David E.; Dean, Cory R.; Young, Andrea (APS March Meeting 2019)
Twisted bilayer graphene (tBLG) near the flat band condition is a versatile new platform for the study of correlated physics in 2D. Resistive states have been observed at several commensurate fillings of the flat miniband, along with superconducting states near half filling. To better understand the electronic structure of this system, we study electronic transport of graphite gated superconducting tBLG devices in the normal regime. At high magnetic fields, we observe full lifting of the spin and valley degeneracy. The transitions in the splitting of this four-fold degeneracy as a function of carrier density indicate Landau level (LL) crossings, which tilted field measurements show occur between LLs with different valley polarization. Similar LL structure measured in two devices, one with twist angle θ=1.08° at ambient pressure and one at θ=1.27° and 1.33GPa, suggests that the dimensionless combination of twist angle and interlayer coupling controls the relevant details of the band structure. In addition, we find that the temperature dependence of the resistance at B=0 shows linear growth at several hundred Ohm/K in a broad range of temperatures. We discuss the implications for modeling the scattering processes in this system.